Optical properties of nematic liquid crystals doped with gold nanorods - Torgova, S.; Pozhidaev, E.; Lobanov, A.; Minchenko, M.; Khlebtsov, B. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2010)
Composites consisting of nematic liquid crystal (5-CB) and gold nanorods have been elaborated and investigated with a polarizing microscope. It was detected that the nanorods form inside the oriented liquid crystal matrix their own self-assembling well-ordered structures. Nanorods ordered structures appear as a result of aligning layers action and provides defects corresponding to the spatial distortion of the nematic liquid crystal director field.